Ethical consumption : practices and identities : a realist approach - Manyukhina, Yana (Routledge studies in critical realism., 2018)
This book engages with the topic of ethical consumption and applies a critical-realist approach to explore the process of becoming and being an ethical consumer. By integrating Margaret Archer's theory of identity formation and Christian Coff's work on food ethics, it develops a theoretical account explicating the generative mechanism that gives rise to ethical consumer practices and identities. The second part of the book presents the findings from a qualitative study with self-perceived ethical food consumers to demonstrate the fit between the proposed theoretical mechanism and the actual experiences of ethically committed consumers. Through integrating agency-focused and socio-centric perspectives on consumer behaviour, the book develops a more comprehensive and balanced approach to conceptualising and studying consumption processes and phenomena. --